Pulmonary hypertension due to interstitial lung disease or chronic obstructive pulmonary disease: a patient experience study of symptoms and their impact on quality of life. (1st April 2021) - DuBrock, Hilary M.; Nathan, Steven D.; Reeve, Bryce B.; Kolaitis, Nicholas A.; Mathai, Stephen C.; Classi, Peter M.; Nelsen, Andrew C.; Olayinka‐Amao, Bimpe; Norcross, Lindsey N.; Martin, Susan A.
Abstract : Pulmonary hypertension resulting from chronic lung disease such as chronic obstructive pulmonary disease and interstitial lung disease is categorized by the World Health Organization as Group 3 pulmonary hypertension. To identify the symptoms and impacts of World Health Organization Group 3 pulmonary hypertension and to capture data related to the patient experience of this disease, qualitative research interviews were undertaken with 3 clinical experts and 14 individuals with pulmonary hypertension secondary to chronic obstructive pulmonary disease or interstitial lung disease. Shortness of breath, fatigue, cough, and swelling were the most frequently reported symptoms of pulmonary hypertension due to chronic obstructive pulmonary disease or interstitial lung disease, and shortness of breath was further identified as the single most bothersome symptom for most patients (71.4%). Interview participants also described experiencing a number of impacts related to pulmonary hypertension and pulmonary hypertension symptoms, including limitations in the ability to perform activities of daily living and impacts on physical functioning, family life, and social life as well as emotional impacts, which included frustration, depression, anxiety, isolation, and sadness. Results of these qualitative interviews offer an understanding of the patient experience of pulmonary hypertension due to chronic obstructive pulmonary disease or interstitial lung disease, including insight into the symptoms and impacts that are most important to patients in this population. As such, these results may help guide priorities in clinical treatment and assist researchers in their selection of patient‐reported outcome measures for clinical trials in patients with pulmonary hypertension due to chronic obstructive pulmonary disease or interstitial lung disease.